The Effect of Attachment Styles on Emotional Regulation Impacting Relationship Satisfaction: An Exploratory Case Study Design - Sargam Arora; Deepika Chamoli (International Journal of Behavioral Sciences, 2025)
This study explores the impact of early attachment experiences, emotional regulation, and relationship dynamics among six participants through a qualitative case study approach. Using thematic and narrative analyses, the research identifies key patterns in emotional suppression, fear of abandonment, trust issues, and self-awareness. Participants' narratives reveal how childhood experiences with caregivers influenced their emotional regulation strategies and attachment styles in adulthood. Findings indicate that those with secure emotional upbringings exhibited healthier coping mechanisms, while those exposed to neglect, trauma, or inconsistent caregiving struggled with emotional dependency, avoidance, or toxic relationship patterns. Thematic analysis highlights core themes, including parental influence, emotional regulation, trust, relational conflicts, and self-awareness. Narrative analysis further examines individual emotional arcs, turning points, and the journey toward emotional growth. The findings highlight how important attachment theory is in determining adult relationships and emotional health. According to the study's findings, developing self-awareness and emotional control might enhance psychological well-being and relationship satisfaction. Additionally, the study highlights the value of supportive family contexts and early emotional education in the development of adaptive coping mechanisms. It also implies that emotional regulation training and attachment repair-focused therapy interventions can improve resilience, personal development, and relationship quality, with important ramifications for counselling psychology and interpersonal development initiatives. All things considered, the research advances our knowledge of attachment healing, emotional development, and the lasting psychological impacts of early relationship experiences.
Keywords: Anxious Attachment; Attachment Styles; Couple Therapy; Relationship Conflict; Relationship Satisfaction; emotional regulation